Migraine aura without headache: transient ischaemic attack or not? - Dennis, M (1992)
Patients with "migraine aura without headache" can be separated from those with transient ischaemic attacks (TIA) on the basis of the onset of symptoms, which is generally gradual and which spread or intensify over minutes or hours, and from the typical migrainous nature of their visual symptoms. Fifty cases were prospectively identified and these were compared with 50 age matched patients with a TIA. Surprisingly, there were no significant differences in the prevalence of vascular risk factors and diseases in the two groups although those with TIAs tended to have more. Only one patient with "migraine aura without headache" suffered a subsequent vascular event (a myocardial infarction). Three patients with TIAs had strokes and two others died from vascular disease. Although the results are not conclusive, they do suggest that patients with the clinical characteristics of "migraine aura without headache" have a low risk of subsequent vascular events, lower than those with TIAs, despite perhaps having similar prevalence of vascular risk factors. Although their risk factors should be treated, patients with "migraine aura without headache" should be reassured and not subjected to inappropriate and potentially hazardous investigations and treatment.